The Risks of A Poor Performance Management System Against Start-Up Companies in Indonesia - Helen Febrina; Denny Tewu (Green Publisher Indonesia, 2025)
This research aims to evaluate the effect of poor performance management on the failure of start-up companies in Indonesia. Start-ups are businesses engaged in developing new technology-based products or services. HR performance management is an important factor in maintaining the survival of start-ups. However, poor performance management can lead to various risks and impact start-up failure. This research uses a risk analysis method with a matrix to identify the risks and impacts of poor performance management on start-up failure. This study involved several respondents from start-up companies (51.7%), conventional private (27.6%), contractors (12.1%), and other workforce (8.6%) in Indonesia. Data was collected through questionnaires and literature, and analyzed using regression analysis. The results showed that poor performance management significantly impacts start-up failure in Indonesia. A total of 84.5% of respondents agreed that a performance management system is very important in a company. The questionnaire results also show some of the reasons start-ups fail in Indonesia, namely: lack of capital/investors (17.2%), losing the competition (5.3%), poor performance management system (58.6%), legality policy (3.4%), products that do not fit the market (13.8%) and poor product quality (1.7%). Analysis of the matrix shows that human resource risk falls into the unacceptable (red) category, which means that mitigation is necessary because it greatly affects the failure or success of a company.